2018
DOI: 10.1007/s40801-018-0137-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes with First-Line Chemotherapy in a Large Retrospective Study of Patients with Metastatic Pancreatic Cancer Treated in a US Community Oncology Setting

Abstract: BackgroundThe combination chemotherapy regimens of nab-paclitaxel plus gemcitabine (nab-p + G) and FOLFIRINOX (FFX) have each demonstrated improved survival compared with gemcitabine monotherapy in clinical trials for metastatic pancreatic cancer; however, limited comparative data exist.ObjectiveThe objective of this study was to compare patient characteristics and clinical outcomes including time to treatment failure and overall survival in patients with metastatic pancreatic cancer receiving first-line chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 12 publications
(19 reference statements)
5
33
1
Order By: Relevance
“…Interestingly, treatment with gemcitabine in combination with capecitabine resulted in similar survival outcomes as treatment with gemcitabine/nab-paclitaxel and even the more intense 5-FU/oxaliplatin/irinotecan treatment. While this had not been demonstrated for gemcitabine/capecitabine before, these findings are in line with recently published retrospective cohort studies that found no differences in OS or TTF between patients treated with 5-FU/oxaliplatin/irinotecan or gemcitabine/nab-paclitaxel in Korean and North American centers [19,20,21]. All three combination therapies were superior to gemcitabine alone or 5-FU/oxaliplatin as first-line treatments (Figure 1 and Figure 2, Table 2) but their benefit was lost as patients discontinued their treatment and it disappeared around the time most patients were off the respective protocol (Figure 2).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, treatment with gemcitabine in combination with capecitabine resulted in similar survival outcomes as treatment with gemcitabine/nab-paclitaxel and even the more intense 5-FU/oxaliplatin/irinotecan treatment. While this had not been demonstrated for gemcitabine/capecitabine before, these findings are in line with recently published retrospective cohort studies that found no differences in OS or TTF between patients treated with 5-FU/oxaliplatin/irinotecan or gemcitabine/nab-paclitaxel in Korean and North American centers [19,20,21]. All three combination therapies were superior to gemcitabine alone or 5-FU/oxaliplatin as first-line treatments (Figure 1 and Figure 2, Table 2) but their benefit was lost as patients discontinued their treatment and it disappeared around the time most patients were off the respective protocol (Figure 2).…”
Section: Discussionsupporting
confidence: 89%
“…We found a total of 493 publications in the electronic databases. A total of 16 studies including 3813 patients (2123 and 1690 of whom were treated with GEM-NAB and FOLFIRINOX respectively), were finally selected for inclusion after exclusion of duplicates and other non-pertinent papers [3,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20]. Fourteen were retrospective case series and two were cohort-studies.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, there is no randomized controlled trial comparing GEM-NAB and FOLFIRINOX in the first-line setting. Secondly, cross-trial comparisons are problematic due to differences in trial designs (inclusion criteria more restrictive for the ACCORD trial) and in patients’ baseline characteristics [6,7]. The ACCORD trial was conducted at academic centers in France and enrolled patients aged ≤75 years with an Eastern Cooperative Oncology Group (ECOG) performance status (PS) ≤1.…”
Section: Introductionmentioning
confidence: 99%
“…Overall median survival for patients with advanced cancer even with treatment is about 10 months. FOLFIRINOX (5-fluorouracil-leucovorin combined with oxaliplatin and irinotecan), is usually given to patients with a good performance status, since it is a relatively toxic regimen [18]. In a retrospective study in several community hospitals patients with a good performance received FOLFIRINOX, while gemcitabine/Abraxane was usually given to patients with a poor PFS; when very poor, gemcitabine was given to a minority as an alternative single agent.…”
Section: Overview Of the Marketmentioning
confidence: 99%